2021
DOI: 10.15252/embj.2020106320
|View full text |Cite
|
Sign up to set email alerts
|

Gut inflammation triggers C/EBPβ/δ‐secretase‐dependent gut‐to‐brain propagation of Aβ and Tau fibrils in Alzheimer’s disease

Abstract: Inflammation plays an important role in the pathogenesis of Alzheimer's disease (AD). Some evidence suggests that misfolded protein aggregates found in AD brains may have originated from the gut, but the mechanism underlying this phenomenon is not fully understood. C/EBPβ/δ‐secretase signaling in the colon was investigated in a 3xTg AD mouse model in an age‐dependent manner. We applied chronic administration of 1% dextran sodium sulfate (DSS) to trigger gut leakage or colonic injection of Aβ or Tau fibrils or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 67 publications
(84 reference statements)
1
35
0
Order By: Relevance
“…Most studies on the gut–brain axis have focused on ascending signals from the intestine, with less attention on signals from the central nervous system [ 37 , 38 ]. In addition, bacteria as nanoparticle carriers can enhance tissue penetration [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on the gut–brain axis have focused on ascending signals from the intestine, with less attention on signals from the central nervous system [ 37 , 38 ]. In addition, bacteria as nanoparticle carriers can enhance tissue penetration [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding of gut pathology preceding motor symptoms is also seen in Tau, Ab and alphasynuclein animal models [17,18]. In these models, it has been hypothesised that the pathology originates in the gut and progresses to involve the CNS when there was (i) a physical connection (intact vagus nerve) and (ii) systemic inflammation [17,18]. When these two conditions were not met, central neuronal pathology did not develop.…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that IBD inflammation may be exacerbated by a disruption of the renin–angiotensin system [ 142 ]. Additionally, inflammation contributes significantly to the etiology of Alzheimer’s disease (AD) by activating C/EBPβ/δ-secretase and causing AD-associated disorders in the gut, which are then transferred to the brain via the vagus nerve [ 143 ]. BACE1 and BACE2 β-secretases have been widely investigated in the context of Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%